Integrating Advocacy and Environmental Education: A Response to Burns & Norris - Niblett, Blair (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2012)
This paper responds to David Burns and Stephen Norris whose article, “Open-minded Environmental Education in the Science Classroom”, appeared in Volume 18(1) of Paideusis. Burns and Norris (2009) suggest an incompatibility between environmental advocacy and science education because they feel that environmental advocacy necessarily promotes particular political agendas that are extra-scientific, and that such agendas subvert the development of open-mindedness (Hare, 1979; 2000; 2003). In this paper, I offer an alternative reading of Hare’s concept of open-mindedness that is more accepting of careful and thoughtful integrations of science education and social advocacy. I offer an epistemological justification that suggests that advocacy in education (in science and elsewhere) is not only compatible with the concept of open-mindedness, but may also serve as a vehicle for its flourishing.